Public Value Management: An Emerging Paradigm in Public Administration - Bojang, Malang B.S. (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
In 1975, Nicholas Henry puts forward five paradigms for public administration. These paradigms demonstrate the historical development of public administration since Woodrow Wilson's famous article. The existence of competing paradigms in public administration enhances theoretical development within the discourse. Public value management has brought a new dimension to the discourse. The purpose of this study is to investigate the paradigmatic shift in public management and to determine if the ‘Public Value Management’ represents an emerging paradigm in public administration. The paper attempts to answer two main questions: (a) Does public value management represent a new paradigm in the field of public administration? (b) Is public value management the future of public administration? To answer these questions, the study followed a historical approach to provide an accurate description and analysis of the current state as well as predicting its future course. Data for this study has been collected through a primary scoping of the literature on public administration. This paper shows that public value is not only an emerging paradigm in public administration but also the future. The study also found out that public value is the next big thing for governments aiming to deliver better public service. The public value paradigm is centered around the needs of the public as citizens, as well as consumers, the creation of value rather than achieving individual outcomes. It is more than the aggregation of individual needs with deliberation as to what constitutes public value at its core. In answering the aforementioned questions, the paper endeavor to establish the focus of public value management paradigm within the public administration field. The study adds value to the literature and theoretical development of public value